Global anomalies on Lorentzian space-times - Schenkel, Alexander; Zahn, Jochen (Springer, 2017)
We formulate an algebraic criterion for the presence of global anomalies on globally hyperbolic space-times in the framework of locally covariant field theory. We discuss some consequences and check that it reproduces the well-known global SU(2) anomaly in four space-time dimensions.